From sea to sky: understanding the sea surface temperature impact on an atmospheric blocking event using sensitivity experiments with the ICOsahedral Nonhydrostatic (ICON) model - S. Christ; M. Wenta; C. M. Grams; C. M. Grams; A. Oertel (Weather and Climate Dynamics)
Blocked weather regimes are an important phenomenon in the Euro-Atlantic region and are frequently linked to extreme weather events. Despite their importance for surface weather, the correct prediction of blocking events remains challenging. Previous studies indicated a link between the misrepresentation of blocking events in numerical weather prediction models and sea surface temperature (SST) biases, particularly in the Gulf Stream region. However, the pathway that links SST in the Gulf Stream region and the downstream upper-level flow is not yet fully understood. To deepen our physical understanding of the link between the Gulf Stream SST and downstream atmospheric blocking, we perform sensitivity experiments with varying SST conditions for an atmospheric blocking event in February 2019. This blocking event, which was associated with a winter heat wave with unprecedented temperatures in western Europe, was both preceded and accompanied by several rapidly intensifying extratropical cyclones originating in the Gulf Stream region and crossing the North Atlantic. Those cyclones and their associated rapidly ascending air streams, so-called warm conveyor belts (WCBs), played a crucial role in the development of the upper-level ridge and the blocking event. The ascent of these WCBs, which connect the lower and upper troposphere, was enhanced by moisture uptake during cold air outbreaks (CAOs) in the Gulf Stream region. In this study, we employ sensitivity experiments with the ICOsahedral Nonhydrostatic Weather and Climate Model (ICON) to assess the impact of intense air–sea interactions during CAOs on WCBs and the downstream ridge. In total five different experiments are used, including idealized and weakened SST gradients and one with increased absolute SST in the Gulf Stream region. Using Eulerian and Lagrangian perspectives, we demonstrate that the SST gradient in the Gulf Stream region affects moisture availability and air temperature in the WCB inflow region and, consequently, WCB ascent. In our case study, stronger SST gradients lead to increased specific humidity and warmer temperatures in the lower troposphere, resulting in more pronounced WCB ascent, while weaker SST gradients are associated with reduced WCB activity. The differences in WCB ascent and outflow properties induced by weakened SST gradients, such as reduced cross-isentropic ascent and outflow heights, subsequently influence the upper-level flow and weaken the downstream ridge. Moreover, experiments with weaker SST gradients show a decrease in cyclone intensity, and vice versa, stronger cyclones are found in experiments with warmer SSTs. To summarize, our results suggest that different SST and SST gradient representations affect the large-scale atmospheric flow via the WCB airstream. Specifically, moisture availability regulated by SST and SST gradients in the WCB inflow region influences subsequent WCB ascent and outflow characteristics, which, in turn, influence the upper-level ridge downstream. The SST in the Gulf Stream region affects WCB characteristics consistently from the inflow, over the ascent to the outflow phase.